Chemoradiation Versus Chemotherapy in Uterine Carcinosarcoma: Patterns of Care and Impact on Overall Survival. (August 2018) - Odei, Bismarck; Boothe, Dustin; Suneja, Gita; Werner, Theresa L.; Gaffney, David K.
Abstract : Objectives: Uterine carcinosarcoma (UCS) is a rare and aggressive cancer with poor survival. Our purpose was to evaluate the patterns-of-care and overall survival (OS) benefit of adjuvant chemoradiation (aCRT) compared with adjuvant chemotherapy (aCT) among UCS patients. Methods: A query was made in the National Cancer Database to identify patients with UCS diagnosed between 2004 and 2012. Factors predictive of OS were determined using univariate and multivariate Cox regression analysis, as well as Kaplan-Meier and log-rank analysis. Propensity-score matching was employed to decrease the potential influence of selection bias. Results: A total of 3538 patients were identified for analysis, consisting of 1787 patients (50.5%) receiving aCT and 1751 (49.5%) receiving aCRT. The median age of patients was 65 years. The majority of patients in our cohort were white (68.6%), on Medicare insurance (47.9%), with >5 cm tumor size (59.9%), and received a lymph node surgery (87.9%). The following factors were predictive of aCRT use: undergoing lymph node surgery (odds ratio, 1.59, P =0.01), and FIGO stage II (odds ratio, 1.71, P =0.01). Median survival for the aCT and aCRT groups was 24 months and 31.3 months, respectively. When compared with aCT alone, aCRT was associated with a benefit in OS on multivariate analysis (hazard ratio, 0.65, P <0.01). Conclusions: When compared with aCT alone, the use of aCRT in UCS patients was associated with a significant OS benefit. Multiple demographic and clinical factors significantly influence the choice of adjuvant therapy in this setting.